Control Strategy of a DVR to Improve Stability in Wind Farms Using Squirrel-Cage Induction Generators - Leon ,Andrés E. (2011)
This work presents a control strategy of a dynamic voltage restorer (DVR) to improve the stability in wind farms based on squirrel-cage induction generators. The DVR controller is tailored to work under unbalanced conditions, which allows overcoming most faults in the power grid. The proposed strategy is capable of balancing voltages at wind farm terminals obtaining several advantages. Firstly, negative-sequence currents are eliminated; thus, overheating, loss of performance, and decreasing of generator useful life are avoided. Secondly, by nullifying negative-sequence voltages, 2ω pulsation in the mechanical torque is prevented, reducing high stress in the turbine mechanical system, especially in the gearbox. The proposed control strategy for the DVR is compatible with farms which already have installed a static VAR compensator. Several scenarios and disturbances, carefully chosen to provide a realistic assessment, have been tested showing the adequacy of the proposed arrangement and controllers.